Flood Risk Assessments Applications and Uncertainties - Diez-Herrero, Andres; Garrote, Julio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In recent years, a considerable volume of technical literature has been published on flood hazard analysis, and more recently, on flood vulnerability and resilience. Nevertheless, there is still a shortage of scientific studies and practical experience of real flood risk assessment (both social and economic), including hazard, exposure and vulnerability analyses and their integration. As there are so few references available, applications of flood risk assessment to the design of preventive measures and early warning systems, landscape and urban planning, civil protection, insurance systems, and risk-based information and education, cannot reach their full potential development. This is because the research products available, such as hazard data and maps, do not serve to ensure the efficient prioritization of mitigation measures or communities at risk. Meanwhile, flooding is the natural disaster that causes the greatest loss on a global scale, and due to climate change, this situation is expected to continue. The research manuscripts involved in this book try to offer flood risk managers new tools, data and maps to improve risk mitigation, both preventive and corrective. A wide variety of topics have been covered, including: flood risk data sources; techniques and methodologies for flood risk analysis; flood risk mapping; or flood risk analysis calibrations.